Bioprospecting Deep-Sea Actinobacteria for Novel Anti-infective Natural Products - Xu, Dongbo; Han, Linna; Li, Chunhui; Cao, Qi; Zhu, Duolong; Barrett, Nolan H.; Harmody, Dedra; Chen, Jing; Zhu, Haining; McCarthy, Peter J.; Sun, Xingmin; Wang, Guojun (Frontiers in Microbiology, 2018)
The global prevalence of drug resistance has created an urgent need for the discovery of novel anti-infective drugs. The major source of antibiotics in current clinical practice is terrestrial actinobacteria; the less-exploited deep-sea Actinobacteria may serve as an unprecedented source of novel natural products. In this study, we evaluated 50 Actinobacteria strains derived from diverse deep water sponges and environmental niches for their anti-microbial activities against a panel of pathogens including Candida albicans, Clostridium difficile, Staphylococcus aureus and methicillin-resistant S. aureus (MRSA), and Pseudomonas aeruginosa. More than half of the tested strains (27) were identified as active in at least one assay. The rare earth salt lanthanum chloride (LaCl3) was shown to be as an effective elicitor. Among the 27 strains, the anti-microbial activity of 15 were induced or enhanced by the addition of LaCl3. This part of study focused on one strain R818, in which potent anti-fungal activity was induced by the addition of LaCl3. We found that the LaCl3-activated metabolites in R818 are likely antimycin-type compounds. One of them, compound 1, has been purified. Spectroscopic analyses including HR-MS and 1D NMR indicated this compound is urauchimycin D. The antifungal activity of compound 1 was confirmed with a minimal inhibitory concentration (MIC) of 25 μg/mL; the purified compound also showed a moderate activity against C. difficile. Additional notable strains are: strain N217 which showed both anti-fungal and anti-bacterial (including P. aeruginosa) activity; and strain M864 which showed potent activity against C. difficile with an MIC value (0.125 µg/mL) lower than those of vancomycin and metronidazole. Our preliminary studies show that deep-sea actinobacteria as a promising source of anti-infective natural products.